Ultrafast Laser to Tailor Material Properties: An Enabling Tool in Advanced Three-dimensional Micromanufacturing - Yves Bellouard (CHIMIA, 2017)
The progress made in ultrafast laser technology towards high repetition rate systems have opened new opportunities in micromanufacturing. Non-linear absorption phenomena triggered by femtosecond pulses interacting with transparent materials allow material properties to be tailored locally and in three dimensions, with resolution beyond the diffraction limits and at rate compatible with fabrication process requirements. In this short article, we illustrate the potential of this technology for manufacturing, and more specifically micro-engineering, with a few examples taken from our own research and beyond.